Pre-trade transparency on the Italian Stock Exchange: a trade size model on panel data - Caterina Lucarelli; Maria Elena Bontempi; Camilla Mazzoli; Anna Grazia Quaranta (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The purpose of this study was to analyze the effects that have been caused by changes in pre-trade transparency upon the behavior of stock traders. We used a trade size model and tested it before, during and after the period when the Italian Stock Exchange introduced a 20-level order book with disaggregated orders. Tick by tick data of the whole set of stocks (up to 277) listed on the Italian Stock Exchange were studied through fixed-effects panel models, within intra day (every 30 minutes and 150 minutes) and daily time frames. Our results indicate that order flows, bidask spreads, levels of risk and some information events differentially affect trade sizes when investors receive better information prior to negotiation. Both (intra day) informed and uninformed traders perating in a more transparent market became more reticent, with reduced trades sizes and higher orders' cancellations. Moreover, it appears that the higher degree of order book disclosure permits traders to downsize their level of risk aversion; i.e. it reduces the 'uncertainty' that would otherwise result in disrupted trading activity under conditions of information opacity.
Keywords: 330